Efeito de terapias de estimulação mecânica e elétrica no fluxo salivar, na mucosite oral induzida por quimioterapia e no nível de citocinas na saliva de pacientes submetidos a TCTH - Tania Mara Pimenta Amaral (2010)
Objective. To evaluate the effects of salivary stimulation therapies on salivary flow, oral mucositis and salivary cytokines levels in patients receiving allogeneic hematopoietic stem cell transplantation. Study Design. Thirty-five patients were randomized into three groups categorized by type of salivary stimulation: Hyperboloid, transcutaneous electrical nerve stimulation (TENS), combination of these two therapies and control group. Resting and stimulated saliva were collected from 7 days before to 14 days after transplantation. Salivary cytokines were assessed by ELISA. Results. The TENS and TENS+Hyperboloid groups were less affected by the reduction of resting salivary flow and also showed a tendency to keep higher rates of stimulated salivary flow in relation to the controls. Therapy groups had lower incidences of oral mucositis in grades 3 and 4. The TENS and TENS+Hyperboloid group tended to show a reduction of MMPs and increased of EGF levels. Conclusion. Salivary stimulation therapies contributed to minimize the reduction of salivary flow and severity of chemotherapy-induced oral mucositis.